Pelatihan menulis paragraf deskripsi bagimahasiswa Jurusan Bahasa Inggris - Amra Ariyani; Sahril Sahril; A. Muliati (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This Community Service aims at helping students ofthe English Department FBS UNM to write descriptionparagraphs by using pictures. The presentation materialconsists of the concepts of writing comprehension and the useof pictures as media to write description paragraphs in Englishin various themes in writing descriptions of people, objects,and places. The methods used are lecturing, discussion,assignment, training, evaluation, and feedback. The result ofthis training is that students of English Department have highenthusiasm and motivation in learning English particularly inwriting description paragraphs. Moreover, the Training ofWriting Description paragraphs by Using Pictures as Mediacan improve students' ability to write description paragraphs,individually, in pairs, or in groups.